A randomized controlled trial of daily sedation interruption in critically ill children - Vet, Nienke J. (Intensive Care Med, 2015)
PURPOSE: To compare daily sedation interruption plus protocolized sedation (DSI + PS) to protocolized sedation only (PS) in critically ill children. METHODS: In this multicenter randomized controlled trial in three pediatric intensive care units in the Netherlands, mechanically ventilated critically ill children with need for sedative drugs were included. They were randomly assigned to either DSI + PS or PS only. Children in both study arms received sedation adjusted on the basis of validated sedation scores. Provided a safety screen was passed, children in the DSI + PS group received daily blinded infusions of saline; children in the PS group received blinded infusions of the previous sedatives/analgesics. If a patient’s sedation score indicated distress, the blinded infusions were discontinued, a bolus dose of midazolam was given and the ‘open’ infusions were resumed: DSI + PS at half of infusion rate, PS at previous infusion rate. The primary endpoint was the number of ventilator-free days at day 28. Data were analyzed by intention to treat. RESULTS: From October 2009 to August 2014, 129 children were randomly assigned to DSI + PS (n = 66) or PS (n = 63). The study was terminated prematurely due to slow recruitment rates. Median number of ventilator-free days did not differ: DSI + PS 24.0 days (IQR 21.6–25.8) versus PS 24.0 days (IQR 20.6–26.0); median difference 0.02 days (95 % CI −0.91 to 1.09), p = 0.90. Median ICU and hospital length of stay were similar in both groups: DSI + PS 6.9 days (IQR 5.2–11.0) versus PS 7.4 days (IQR 5.3–12.8), p = 0.47, and DSI + PS 13.3 days (IQR 8.6–26.7) versus PS 15.7 days (IQR 9.3–33.2), p = 0.19, respectively. Mortality at 30 days was higher in the DSI + PS group than in the PS group (6/66 versus 0/63, p = 0.03), though no causal relationship to the intervention could be established. Median cumulative midazolam dose did not differ: DSI + PS 14.1 mg/kg (IQR 7.6–22.6) versus PS 17.0 mg/kg (IQR 8.2–39.8), p = 0.11. CONCLUSION: In critically ill children, daily sedation interruption in addition to protocolized sedation did not improve clinical outcome and was associated with increased mortality compared with protocolized sedation only.